Patient-Reported Outcomes in Colorectal Surgery - Maspero, Marianna; Hull, Tracy (Clinics in Colon and Rectal Surgery, 2023)
Given the increased life expectancy and improvements in the treatment of colorectal patients, the success of a treatment course can no longer be determined only by objective outcomes. Health care providers ought to take into consideration the impact an intervention will have on the quality of life of patients. Endpoints that take into account the patient's perspective are defined as patient-reported outcomes (PROs). PROs are assessed through patient-reported outcome measures (PROMs), usually in the form of questionnaires.PROs are especially important in colorectal surgery, whose procedures can often be associated with some degree of postoperative functional impairment.Several PROMs are available for colorectal surgery patients. However, while some scientific societies have offered recommendations, there is no standardization in the field and PROMs are seldom implemented in clinical practice. The routine use of validated PROMs can guarantee that functional outcomes are followed over time; this way, they can be addressed in case of worsening.This review will provide an overview of the most commonly used PROMs in colorectal surgery, both generic and disease specific, as well as a summary of the available evidence in support of their routine utilization.
Keywords: patient-reported outcomes; patient-reported outcome measures; colorectal surgery